An Interprofessional Curriculum to Advance Relational Coordination and Professionalism in Early-Career Practitioners - Katherine B. Valenziano; Susan A. Glod; Sharon Jia; Andrew Belser; Brent Brazell; Cheryl Dellasega; Linda Duncan; Michelle Farnan; Paul Haidet; Jan Phillips; Daniel Wolpaw; Peter W. Dillon (Association of American Medical Colleges, 2018)
Introduction We created a curriculum to help new physicians and nurses develop skills in interprofessional collaboration. This modular, team-based curriculum for early practitioners delivered training in the five following skill areas: listening for meaning, soliciting another's perspective, negotiating a transparent plan of care, attending to nonverbal communication and microaggression, and speaking up the hierarchy. Methods We brought first-year medical and surgical residents and new nurses together for a 2-hour session monthly for 5 months. Each session began with an interactive large-group presentation, followed by small-group activities covering one of the five skill areas above, which had been identified as critical to interprofessional collaboration by national organizations. We measured relational coordination (RC), a validated measure of how well teams work together, before and after the curriculum was administered. We also obtained qualitative data from participant interviews and end-of-session evaluations. Results Participants reported that the program helped them gain an understanding of each other's roles and workflow challenges. They felt that the curriculum allowed for the cultivation of professional relationships outside the clinical environment, which improved collegiality via gains in rapport and empathy towards each other. Nurses noted increased approachability of their physician colleagues after participation. RC scores improved for the entire cohort (p = .0232). Nurses had statistically higher RC gains than interns did (p = .0055). Discussion Curriculum participants demonstrated improved RC scores and reported increased rapport with and empathy for each other. Curriculum development in this area is important because it may lead to better team-based patient care.